Strategi Pengelolaan Program Promosi Kesehatan Oleh Mahasiswa STIKes Husada Borneo Dalam Organisasi Kampus - Hermawan, Dedy (CV. Multi Kreasi Media, 2024)
This study aims to explore strategies for managing health promotion programs conducted by university students, focusing on STIKes Husada Borneo. The findings reveal that managing such programs faces various challenges, including limited resources, lack of management experience, and insufficient standardized evaluation. However, significant potential lies in engaging students as agents of change in promoting health. A data-driven approach is required to ensure the program is more relevant to students' needs. Furthermore, structured training and intensive mentoring can enhance students' capacity to plan, execute, and evaluate programs effectively. Collaboration with external institutions, such as the Health Department and non-governmental organizations, serves as a key strategy to strengthen the program through additional resource support. The campus can act as a facilitator to bridge the relationship between students and external parties, ensuring the sustainability of such collaborations. These programs also require valid evaluation tools to measure their impact on students' knowledge, attitudes, and behaviors. With proper implementation, health promotion programs will not only improve students' well-being but also serve as models for adoption by other educational institutions. In conclusion, these programs play a crucial role in shaping a health-conscious younger generation, supporting the Ministry of Health's mission to build a healthier and more productive society.